The development of mentalization in adolescence and its dysfunctions - Barkauskienė, Rasa; Čekuolienė, Danguolė; Adler, Asta; Gervinskaitė-Paulaitienė, Lina (Psichologija, 2017)
Numerous important changes that occur in social cognition during adolescence determine the progressively growing self-awareness in adolescents (Harter, 2012) and the better understanding of their own and other people’s emotions. More importantly, the need and ability to control emotional processes in the interpersonal context and in the self notably change as well. The developmental tasks of adolescents determine the shift in their interactions from the family of origin to peers. Thus, the ability to mentalize, which facilitates an understanding of the self and the behaviors of others in terms of mental states, becomes crucial (Fonagy, Gergely, Jurist, & Target, 2005). Mentalization research traditionally focused on the developmental context – early attachment relationships. However, in adolescence, the directions of the research inevitably become more complex and broad due to the changes during adolescence per se. Therefore, the understanding of mentalization in adolescence has a strong link to the wider field of social cognition constructs. Regardless of the unequivocal agreement on the importance of the establishment of the ability to mentalize in adolescence, any consistent analysis of mentalization during this period is still sparse. The article proposes to fill this gap by analyzing the multidimensional construct of mentalization in the context of theoretical and empirical data in psychodynamic theory, developmental psychology, developmental psychopathology and neuroscience. The central focus of the article is the examination of the polarized dimensions of the mentalization construct: cognitive vs. affective, self vs. other mentalization in adolescence. A further analysis, based on theory and rather limited available research, turns the attention to the dysfunction of mentalization and its links to different manifestations of psychopathology during adolescence. The data allow us to consider at least two aspects in theoretical perspective on linking mentalization dysfunction to psychopathology in adolescence: 1) The status quo of the ability to mentalize based on the earlier experience of the individual; 2) Possible links of mentalization dynamics during adolescence in relation to psychopathology. Particular attention is drawn to the meaning that the dysfunction of mentalization may have to the psychopathology and difficulties in adolescents. Special emphasis is made on the imbalance found in the various dimensions of mentalization and/or the lack of their integration in general.
Keywords: mentalization; adolescence; theory of mind; social cognition